Modern Leadership and Managerial Competence of Islamic Primary School Staff: Kepemimpinan Modern dan Kompetensi Manajerial Tenaga Kependidikan Sekolah Dasar Islam - Mustakim, Sulfiani; Nurdin, Muh. Nur Islam; Fitria, Faning Maulida; Susilawati, Susilawati; Novitasari, Kartika (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Educational institutions in the twenty-first century face rapid digital transformation that requires leadership approaches beyond conventional managerial practices. Specific Background: In Islamic primary schools, transformational leadership and digital leadership have emerged as key dimensions of modern leadership applied by school principals to support administrative and managerial functions of educational personnel. Knowledge Gap: Despite growing scholarly attention to leadership styles, empirical evidence that jointly examines transformational and digital leadership in relation to managerial competence of educational staff in Islamic primary schools remains limited. Aims: This study aims to analyze the contribution of transformational leadership and digital leadership to the managerial competence of educational personnel at SD Islam Al-Azhar 38 Bantul. Results: Using a quantitative ex post facto design with total sampling of 34 educational staff members, the findings demonstrate that transformational leadership and digital leadership simultaneously explain 87.8 percent of the variance in managerial competence, with digital leadership showing a dominant role, while transformational leadership presents a non-significant coefficient. Novelty: The study integrates two dimensions of modern leadership within the specific context of Islamic primary school educational personnel, highlighting digital leadership as a central managerial driver. Implications: These findings suggest that strengthening digital leadership practices, supported by adequate infrastructure and continuous professional development, is essential for advancing managerial competence and improving administrative governance in Islamic primary education. Highlights • Transformational and digital leadership jointly account for a high proportion of managerial competence variance• Digital leadership demonstrates a dominant contribution within a school digitalization context• Islamic primary schools benefit from integrated modern leadership practices supported by digital systems Keywords Transformational Leadership; Digital Leadership; Managerial Competence; Educational Personnel; Islamic Primary School